Designing a bench for testing medically and technically an information and measuring system for multi-frequency electrical impedance tomography of human lungs - Aleksanyan, Grayr (Eastern-European Journal of Enterprise Technologies, 2021)
This paper solves the problem of developing and creating multifunctional tools for conducting research into systems of multi-frequency electrical impedance tomography of human lungs. A test bench consisting of modern medical equipment, simulating pre-and postoperative environments to create conditions that are most similar to clinical ones, under which it is planned to operate multi-frequency electrical impedance tomography systems, was proposed and manufactured. This makes it possible to reduce significantly the time for approbation, testing, and elimination of practical inaccuracies and problems of clinical application of the developed medical and technical facilities. A positive result is achieved due to the possibility of forming new test plans with specified conditions and different levels of complexity. This enables enhancing the effectiveness of subsequent clinical tests on patients who are treated in a resuscitation unit or an intensive care unit. The operability of the bench is proved by the repeatability of obtained results of monitoring ventilation and perfusion for each examined person, the continuity of dynamic visualization of the breathing process, as well as a high degree of correlation of obtained values of differences of potentials with the readings of a bedside monitor of a patient. An information and measuring system of multi-frequency electric impedance tomography of human lungs, developed by the author earlier, was used as the EIT device. The EIT tests were performed for the frequency range of 50 kHz – 400 kHz at a current of 5 mA. All experimental studies involved volunteers who gave written information consent to participate in the tests. The results of the research show that the proposed bench can be used in practice to solve a wide range of scientific and applied problems in the field of electrical impedance tomography